Spontaneous virus reactivation in cattle chronically infected with bovine leukemia virus - Jaworski, Juan Pablo (2019)
Background: The absence of virus expression during the chronic stage of bovine leukemia virus (BLV) infection and its reactivation upon ex vivo culture has become a long-lived Dogma. During the chronic stage of BLV infection the immune response limits viral replication and the mitotic division of latently infected cells, carrying BLV provirus, allows viral expansion and disease progression towards a lymphoproliferative disorder. Several stressor factors have been associated with animal production and handling. As natural mediator of stress, glucocorticoids are strong immunosuppressive agents; moreover, they can bind long-terminal repeat region of retroviruses and induce viral expression. In the present study, we present a case report describing the spontaneous reactivation of BLV infection in naturally infected cattle. Case presentation: In order to investigate if virus reactivation occurred in vivo during the course of BLV infection, we followed up for 328 days one Holstein cow (> 3 years) chronically infected with BLV which presented high-proviral loads. This animal was neither lactating nor pregnant. Furthermore, we investigated if a stressor stimulus, in this case the administration of a synthetic glucocorticoid (dexamethasone), could impact the course of BLV infection in three additional cattle. For the first time, we observed a high level of BLV transcripts in a total of four cattle chronically infected with BLV. The detection of viral transcripts corresponding to pol gene strongly suggests virus reactivation in these animals. Interestingly, this simultaneous virus reactivation was unrelated to dexamethasone treatment. Conclusions: We reported for the first time spontaneous and high level of BLV transcriptional activation in cattle chronically infected with BLV. Although virus reactivation was unrelated to dexamethasone treatment, other stressor stimuli might have influenced this outcome. Future studies will be necessary to understand these observations, since the spontaneous virus reactivation presented here might have implications on BLV pathogenesis and transmission.